Tradisi Pembacaan Doa Ayat Kursi Dalam Kegiatan Itikaf 10 Hari Akhir Ramadhan (Studi Living Qur’an Di Masjid Attaqwa Kel. Bahagia Kec. Babelan Kab. Bekasi) - Ahmad, Khoirul Anwar; Nawawi, Abd. Muid; Mulyani, Mulyani (Syntax Corporation, 2025)
This research aims to discuss the tradition of reciting the invocation of ayat kursi which is carried out during the itikaf activities in the last 10 days of Ramadhan. This research was conducted at the Attaqwa Mosque, Bahagia Village, Babelan District, Bekasi Regency. This research uses qualitative and sociological phenomonological methods as an approach. Primary data sources in this research come from documents held by related institutions and answers from related parties who were interviewed. Meanwhile secondary data sources come from various scientific references related to this research. The Muslim community is certainly no stranger to the “living Qur’an”. There are several opinions regarding the study of the living Qur’an, the first opinion is from Sahiron Syamsuddin stating that the living Qur’an is “the text of the Qur’an that lives in society”. Meanwhile, the second opinion is from M. Mansur who states that the living Qur’an is “the Qur’an in Everyday Life, this phenomenon has occurred and in essence the meaning and function of the Qur’an can be understood and experienced by the Muslim community”. Meanwhile, the third opinion emerged from Heddy Shri Ahimsa-Putra who clarified the meaning of the living qur’an into three categories. First, the Prophet Muhammad as the ‘living qur’an”. Second, the function of the Al-Qur’an in everyday life. Third, implementation of the meanings of the Al-Qur’an. This research shows that the participants of itikaf for the last 10 days of Ramadhan at the Attaqwa Mosque tried to interpret the activity of reading the invocation of ayat kursi in a social and qur’anic manner with the aim of getting a pleased and reward from Allah Swt. by reading the ayat kursi, the invocation of ayat kursi, other verses and surahs, you can also hope for the virtues of the ayat kursi. The mu’takifîn feel confident that when they read the ayat kursi and the invocation of ayat kursi, they will receive an abundance of pleased and grace from Allah Swt. in the form of fadhîlah the invocation of ayat kursi. Researcher also found that the meaning of the mu’takifîn congregation regarding the tradition of reciting the invocation of ayat kursi cannot be separated from the meaning of the original text and its priorities. However, researcher also found sustainable benefits and other benefits from reading this invocation of ayat kursi. Thus, the traditions carried out do not conflict with Islamic law.